Trends in the prevalence of concurrent anaemia and stunting among infants and young children in Rwanda: a cross-sectional study from 2010 to 2020 - Mathieu Nemerimana; Mojeed Akorede Gbadamosi (Global Health Action, 2025)
Background Concurrent anaemia and stunting (CAS) pose severe public health risks in low- and middle-income countries, affecting child health and development. Objectives To determine trends in CAS prevalence and associated factors among infants and young children aged 6–23 months in Rwanda. Methods Analyses of nationally representative samples from the Rwanda Demographic and Health Surveys (RDHS) of 2010, 2014/15, and 2019/20 were conducted. Participants’ characteristics, trends, and prevalence of CAS were analysed using frequencies and percentages. Multivariable binary logistic regression analyses were used to assess factors associated with CAS. Results The prevalence of CAS among children aged 6–23 months in Rwanda declined from 21.3% in 2010 to 16.9% in 2019/20 (p = 0.005). Significant factors associated with CAS included child’s age above 12 months, male sex, small/very small birth size, breastfeeding initiation 1 day post-birth, inadequate minimum acceptable diet, history of cough 2 weeks prior to the survey, multiple births, being from a mother with no or only primary education, mother aged below 20 years, mother with no iron supplementation during pregnancy, maternal anaemia, resident of an eastern province, resident of high altitude areas (>2000 m), low household wealth and unimproved toilet facilities. Conclusions This study reveals persistent CAS among infants and young children in Rwanda. CAS was associated with various child, maternal, and household-related factors. Despite a notable decline in CAS prevalence in Rwanda over the past decade, CAS remains a significant public health issue, requiring targeted interventions.